Investigation and analysis of corn cob, coir pith with wood plastic composites. (2021) - Pratheep, V.G.; Priyanka, E.B.; Thangavel, S.; Jason Gousanal, J.; Bijoy Antony, P.T.; Kavin, E.D.
Abstract: The optimization of the resources is a must to overcome the everyday needs of the people. Hence the present research deals with developing environmental and eco-friendly Wood Plastic Composites (WPC) using the corn cob powder and coir pith powder. The composite is made with wood powder, corn cob powder and coir pith which is the most waste produced. The present research work makes use of agriculture residue. Here the hybridized wood powder, hybridized coir pith and corn cob powder are taken as the reinforcement material for the composite. PVC resin and PPA Hardener binds these powder materials to a single structure. This composite with the PVC matrix is obtained by the compression molding method as it undergoes curing for a minimum of 8 h. They are mixed with different proportions and their properties vary with their powder proportions. The percentage of powder loading in this research is maintained at 20%. From the resultant mechanical tests, it is inferred that the tensile and flexural strength rises with the incorporation of corn cob in the proportion of equal ratio to which wood powder is added in the composition. Further, fabricated wood composite shows higher impact strength as compared to other specimens taken for analysis due to the content of both the corn cob and coir pith powder.